Integrated approach for selecting efficient Saccharomyces cerevisiae for industrial lignocellulosic fermentations: importance of yeast chassis linked to process conditions - Costa, Carlos E. (2017)
In this work, four robust yeast chassis isolated from industrial environments were engineered with the same xylose metabolic pathway. The recombinant strains were physiologically characterized in synthetic xylose and xylose-glucose medium, on non-detoxified hemicellulosic hydrolysates of fast-growing hardwoods (Eucalyptus and Paulownia) and agricultural residues (corn cob and wheat straw) and on Eucalyptus hydrolysate at different temperatures. Results show that the co-consumption of xylose-glucose was dependent on the yeast background. Moreover, heterogeneous results were obtained among different hydrolysates and temperatures for each individual strain pointing to the importance of designing from the very beginning a tailor-made yeast considering the specific raw material and process.